2016
DOI: 10.1136/bjophthalmol-2016-308659
|View full text |Cite
|
Sign up to set email alerts
|

The cataract situation in Suriname: an effective intervention programme to increase the cataract surgical rate in a developing country

Abstract: The cataract situation in Suriname is well under control since the implementation of the new intervention programme. Important factors contributing to this success were the introduction of phacoemulsification, intensive training, and improvement in the affordability and accessibility of cataract surgery. The proportion of poor outcomes was still >5%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 14 publications
(20 reference statements)
0
6
0
Order By: Relevance
“…Two studies demonstrated improvement in patient outcomes: decreased mortality (odds ratio [OR] = 2.09, P = .006) for trauma patients directly admitted to referral hospitals in Malawi versus indirect transfers and decreased complications (lower rate of poor visual acuity for centralized care, 8.5% vs 33.3%) from cataract extraction following an investment in training and infrastructure at a centralized eye center in Suriname (Table 4). 53,56 No negative or equivocal outcomes were noted for the regionalization studies.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Two studies demonstrated improvement in patient outcomes: decreased mortality (odds ratio [OR] = 2.09, P = .006) for trauma patients directly admitted to referral hospitals in Malawi versus indirect transfers and decreased complications (lower rate of poor visual acuity for centralized care, 8.5% vs 33.3%) from cataract extraction following an investment in training and infrastructure at a centralized eye center in Suriname (Table 4). 53,56 No negative or equivocal outcomes were noted for the regionalization studies.…”
Section: Resultsmentioning
confidence: 95%
“…75,76 Community outreach was an essential component of the majority of regionalization interventions in this study, emphasizing the importance of community engagement. 52,54-56 Mobile surgical camps or intermittent travel to lower-level hospitals may be implemented to improve accessibility to these highly complex services. 66…”
Section: Discussionmentioning
confidence: 99%
“…Several countries were found to have a significant increase in CSRs, such as Sri Lanka, Suriname. This is reflective of the health policy changes that re‐prioritized eye care services, such as investment in phacoemulsification, intensive training and improvement in the accessibility and affordability of cataract surgery to meet the needs for reducing a substantial backlog of unoperated cataract with VI cases . Conversely, other countries were found to have decreased CSRs such as Kenya, Togo and Sierra Leone.…”
Section: Discussionmentioning
confidence: 99%
“…This is reflective of the health policy changes that reprioritized eye care services, such as investment in phacoemulsification, intensive training and improvement in the accessibility and affordability of cataract surgery to meet the needs for reducing a substantial backlog of unoperated cataract with VI cases. 38,39 Conversely, other countries were found to have decreased CSRs such as Kenya, Togo and Sierra Leone. This may be explained by incomplete execution of eye care programmes at a national level, poor patient education and outdated practices such as "couching," and restricted resource allocation to eye care due to competing health issues.…”
Section: Figurementioning
confidence: 99%
“…The previous arrangement with The Netherlands for cardiac surgery missions to Suriname has resulted in the built-up of sufficient capacity to perform most of these procedures by the cardiologists of the Academic Hospital Paramaribo. Similarly, patients with poor eye sight due to cataract who were initially operated in Cuba, are now treated in Suriname by specialists from the Suriname Eye Center [53].…”
Section: Health Infrastructurementioning
confidence: 99%